2006
DOI: 10.1097/01.prs.0000201460.54187.d7
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating Axons Emerge Far Proximal to the Coaptation Site in End-to-Side Nerve Coaptation without a Perineurial Window Using a T-Shaped Chamber

Abstract: The authors could not locate the site of axonal sprouting in end-to-side neurorrhaphy without a perineurial window; however, this study cast doubts on current hypothesis on the mode of axonal regeneration in end-to-side neurorrhaphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 26 publications
5
29
1
8
Order By: Relevance
“…Several authors have concluded that axonal damage to the donor nerve is required to induce motor collateral sprouting but may not be required to induce sensory sprouting in end-to-side neurorrhaphy [1,12,28,29]. In a recent review by Dvali et al, the authors concluded that the degree of motor axonal sprouting following end-to-side repairs depends upon the degree of axonal damage, while sensory sprouting was less dependent on the presence of injury [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have concluded that axonal damage to the donor nerve is required to induce motor collateral sprouting but may not be required to induce sensory sprouting in end-to-side neurorrhaphy [1,12,28,29]. In a recent review by Dvali et al, the authors concluded that the degree of motor axonal sprouting following end-to-side repairs depends upon the degree of axonal damage, while sensory sprouting was less dependent on the presence of injury [8].…”
Section: Discussionmentioning
confidence: 99%
“…However there are some authors who still believe that the ETS with sutures could harm the donating nerve, especially small dimension nerves 8,9 .…”
Section: Many Authors Have Recently Enhanced the Results Of End-mentioning
confidence: 99%
“…According to Akeda et al 8 , the process of axonal sprouting in an intact nerve, such as ETS with fibrin glue, is slower and in smaller scale that in a nerve with violated epineurium. In an ETE, for example, the axons are identified in the repair point in about two days; in an ETS, with sutures, such event is only detected from the fifteenth day on.…”
Section: Resultsmentioning
confidence: 99%
“…However, to date there is no consensus on the realization of reanimation of the facial paralysis in one or two surgical stages 2,4,9 . In this context, the main objective of this experimental research was to compare aspects of muscle reinnervation with nerve graft in one and two surgical stages, using the end-to-side neurorrhaphy, because this technique of neurorrhaphy has the great advantage of not injuring the epineurium of donor nerve [17][18][19][20][21][22] and, consequently, any nerve could potentially be used as a donor 22 . A comprehensive review of pertinent English literature (Medline and Embase databases)…”
Section: Discussionmentioning
confidence: 99%
“…The end-to-side neurorrhaphy without donor nerve lesion, introduced in 1992 by Viterbo et al 17 , has been increasingly used [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and has the advantage of not injuring the donor nerve.…”
Section: Introductionmentioning
confidence: 99%